A novel prognostic nomogram predicts premature failure of kidney allografts with IgA nephropathy recurrence - Bednarova, Kamila; Mjøen, Geir; Hruba, Petra; Modos, Istvan; Voska, Ludek; Kollar, Marek; Viklicky, Ondrej (Nephrology, dialysis, transplantation, 2023)
BACKGROUND: Recurrence of immunoglobulin A nephropathy (IgAN) limits graft survival in kidney transplantation. However, predictors of a worse outcome are poorly understood. METHODS: Among 442 kidney transplant recipients (KTRs) with IgAN, 83 (18.8%) KTRs exhibited biopsy-proven IgAN recurrence between 1994 and 2020 and were enrolled in the derivation cohort. A multivariable Cox model predicting allograft loss based on clinical data at the biopsy and a web-based nomogram were developed. The nomogram was externally validated using an independent cohort (n = 67). RESULTS: Patient age <43 years {hazard ratio [HR] 2.20 [95% confidence interval (CI) 1.41-3.43], P < .001}, female gender [HR 1.72 (95% CI 1.07-2.76), P = .026] and retransplantation status [HR 1.98 (95% CI 1.13-3.36), P = .016] were identified as independent risk factors for IgAN recurrence. Patient age <43 years [HR 2.77 (95% CI 1.17-6.56), P = .02], proteinuria >1 g/24 hours [HR 3.12 (95% CI 1.40-6.91), P = .005] and C4d positivity [HR 2.93 (95% CI 1.26-6.83), P = .013] were found to be associated with graft loss in patients with IgAN recurrence. A nomogram predicting graft loss was constructed based on clinical and histological variables, with a C statistic of 0.736 for the derivation cohort and 0.807 for the external validation cohort. CONCLUSIONS: The established nomogram identified patients with recurrent IgAN at risk for premature graft loss with good predictive performance.
Keywords: retrospektivní studie; Allografts; Humans; lidé; Graft Survival; Kidney; Retrospective Studies; alografty; recidiva; Female; Adult; prognóza; Prognosis; Nomograms; ženské pohlaví; IgA nefropatie; Glomerulonephritis, IGA; dospělí; ledviny; přežívání štěpu; Recurrence; nomogramy